Parking futures: Curbside management in the era of 'new mobility' services in British and Australian cities. (February 2020) - Marsden, Greg; Docherty, Iain; Dowling, Robyn
Highlights: This is a critical examination of the impacts of new mobility services on curbsides. There is a continued need for state intervention to manage the tensions between movement and place. It shows the importance of processes of recodification of curb use in shaping the transition to more automated futures. Diversification and intensification of use of the curb mean that conditions will deteriorate before they improve. Abstract: The curb is the critical site of interaction between people and vehicles, and between movement and place. Despite decades of debate about how to manage the allocation of space and time to different users, the curb remains a highly contested space which the state finds hard to govern effectively. New pressures on the curb are already apparent: recent changes to the mobility system have resulted in an intensification of use with growth in home delivery and servicing traffic and greater use by ridehailing services. Simultaneously there is a diversification of demands with requirements for bespoke access for new mobility services and innovations such as car and bike share and electric charge points. Looking ahead, a range of actors are developing visions of a shift from individual ownership of cars to shared but intensively used highly automated fleets. The balance of parking, pick up and drop off and movement could be radically different in future. Drawing on literature on the literature on boundary objects, this paper explores the way in which different user groups seek to ensure their own interests are represented at the curb. Through examination of the changing nature of streets in-use, the paper reveals the on-going processes of reallocating and appropriation of curb space. The formal and informal codification of curb use stimulated by interests operating at national and international scales marginalises some user groups and works against place-based planning approaches. The paper makes the case for public policy to reassert itself in the curb debate to avoid a significant decline in conditions and to seek to balance commercial and social interests.